Efficient palladium-catalysed enamide synthesis from enol triflates and enol tosylates - Willis, M; Brace, G; Holmes, I (2005)
Catalysts generated from Pd2(dba)3 and biphenyl ligands 4 and 7 efficiently promote the coupling of amides and carbamates with unactivated vinyl triflates and tosylates, to provide enamides in good to excellent yields. © Georg Thieme Verlag Stuttgart.